Respuesta :

gmany

Answer:

x = m - z

Step-by-step explanation:

z = m - x       add x to both sides

z + x = m - x + x

z + x = m            subtract z from both sides

z - z + x = m - z

x = m - z

The value of x is expressed as m - z

Equations  are expressions separated with an equal to sign.

Given the equation

Z = m-x

Add x to both sides

Z+x = m - x + x

Z+x = m

Subtract z from both sides

z+x-z = m-z

x = m - z

Hence the value of x is expressed as m - z

Learn more here: https://brainly.com/question/20675643

ACCESS MORE

Otras preguntas